CARDIOPULMONARY RESUSCITATION: A NEW PERSPECTIVE - V. A. Sulimov; Yu. V. Gavrilov; E. O. Okisheva (Рациональная фармакотерапия в кардиологии, 2015)
At the present there are principles of cardiopulmonary resuscitation (CPR) which are reflected in the recommendations of the AHA and ESC of 2010. They include strict rules on well-timed and proper closed-chest cardiac massage. According to these rules chest compressions should be repeated at least 100 times per minute at a depth of not less than 5 cm. To comply with the standards is not easy even for skilled staff, operator tiredness quickly leads to decrease in CPR quality. Various mechanical devices for closed-chest cardiac massage are used nowadays. One of them is LUCAS system. In some studies LUCAS system showed an efficacy and safety comparable with manual closed-chest cardiac massage. Design features of the LUCAS device do not disturb other life maintaining activities — defibrillation, mechanical ventilation. The device permeability for X-rays makes possible the use of LUCAS in cath labs, if CPR is needed during the intervention procedure. LUCAS system can serve as an alternative tool for CPR. It can be used in intensive care units, as well as be at the disposal of special emergency teams.